Políticas para as diferenças: gênero, raça e sexualidade como questões de Estado (1996-2022) - Paiva, Gabriela Pandeló (2024)
The end of the Military Dictatorship and the promulgation of the 1988 Federal Constitution, mark a change in the profile of Brazilian social demands, creating legitimization for the State to dedicate itself to developing social protection policies. This work proposes to analyze this period based on the hypothesis that there was an upward movement, related to the Social-liberal and New Developmentalist phases, and a moment of regression referring to the Ultraliberal Conservative period led by Michel Temer and Jair Bolsonaro. Therefore, this work analyzes the gender, race and sexuality policies proposed based on the investigation of their respective National Plans and other protective instruments developed over the period 1996-2022. The justification is that these minorities constitute numerical majorities, and the free exercise of sexuality and gender identity belongs to the scope of civil liberties and must be guaranteed by law. It is concluded that the increase in social protection and access to citizenship for social minorities at a time of economic growth promoted a conservative, ultraliberal and Christian reaction that dismantled this structure, and that in turn was aggravated by the COVID-19 pandemic, resulting in the loss of the 2022 elections.